Biomolecular nonlinear dynamic mechanisms as a foundation for human traits of information processing machine - Nicholas G. Rambaidi (Discrete Dynamics in Nature and Society)
A pseudo-biological paradigm in information processing launched by McCulloch and Pitts in the early 1940s has been advanced during the last decades. Different attempts were made based on these developments to design operational information processing devices capable of solving problems of high computational complexity.